ANALISIS KESEIMBANGAN PENGARUH INFLASI TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA WANITA DI INDONESIA - Ayu Arini, Gusti; Suprapti, Ida Ayu Putri; Sutanto, Himawan; Handayani, Tuti (Elastisitas : Jurnal Ekonomi Pembangunan, 2023)
This research aims to analyze and prove the influence of the inflation variable on the level of female labor force participation in Indonesia. The type of research used is explanatory research, the data collection method used in this research is a case study. The research was conducted in Indonesia in the 2000-2021 period, data sources include Bank Indonesia, BPS, and Bappenas.